ANALISIS SALURAN PEMASARAN KOPI (Studi Kasus: Kecamatan Lintong Nihuta, Humbang Hasundutan, Sumatera Utara) - Sarah Gracia; E D Martauli E D Martauli (JURNAL AGROTEKNOSAINS, 2021)
Coffee is a plantation commodity that is included in the strategic commodity category in Indonesia. Indonesia is the world's fourth largest coffee exporter with a market share of around 11% in the world. In this research, coffee marketing analysis was conducted in Dolok Sanggul, Humbang Hasundutan, North Sumatra. Precisely in the District of Dolok Sanggul is currently being promoted as one of the leading commodities that continue to be developed. There are two marketing channels for Arabica Coffee Beans in Lintong Nihuta District, namely: Channel 1 (one), namely; farmers sell coffee to village collectors, village collectors sell to sub-district traders, sub-district traders sell to district traders and finally district traders sell to district traders (exporters), Channel 2 (second), namely; coffee farmers sell coffee to sub-district traders, sub-district traders sell to district traders (exporters). With the marketing margin value of marketing channel I of Rp 23,000 and marketing margin of channel II of Rp 20,000. This shows that the second marketing channel is more efficient, because the marketing margin is smaller than other marketing channels and the number of marketing agencies involved is less. The value of farmer's share in marketing channel I is 42.2%, in marketing channel II 50%. So it can be concluded that marketing channel II is the marketing channel with the highest value. Each marketing agency plays at least 3 functions. Some marketing agencies carry out the entire marketing function. Marketing costs, marketing margins, share margins and price spreads in each marketing channel are different.